Critical Care Management of Systemic Lupus Erythematosus with Autoimmune Hemolytic Anemia and Thrombocytopenia in Pregnancy: A Case Report - Liliriawati Ananta Kahar (Eduvest - Journal of Universal Studies, 2025)
Autoimmune diseases like Systemic Lupus Erythematosus (SLE) in pregnancy pose significant management challenges, particularly when complicated by severe hematological manifestations such as autoimmune hemolytic anemia (AIHA) and thrombocytopenia, which necessitate intensive care. This case report aims to describe the comprehensive intensive care management and outcomes of a pregnant patient with suspected SLE presenting with severe AIHA and thrombocytopenia. A qualitative case study design was employed. The research focused on a single, purposively selected 21-year-old primigravida at 30–31 weeks gestation. Data were collected from medical records and analyzed descriptively to document the patient's clinical presentation, diagnostic workup, multidisciplinary therapeutic interventions, and subsequent progress. The patient presented with severe anemia (Hb 5 g/dL) and thrombocytopenia (platelets 125,000/mm³). Management involved pregnancy termination, multiple packed red cell transfusions, high-dose corticosteroids (methylprednisolone), and mechanical ventilation. Following this aggressive regimen, the patient was successfully extubated on day 3 with hemodynamic stability and improved hematological parameters (Hb 9.6 g/dL). This case highlights that a multidisciplinary approach combining prompt delivery, immunosuppression, and intensive supportive care is crucial for favorable maternal outcomes. It underscores the importance of early recognition and aggressive treatment of autoimmune complications in pregnancy to prevent life-threatening consequences.